High-strength wear-resistant powder metallurgy bearing
By using specific proportions of copper, aluminum, silicon, barium, chromium, nanomanganese boronide and nanotantalum carbide in the bearing, combined with powder metallurgy technology, the existing bearings are solved at low speed, large loads and impact load conditions. The problem of insufficient strength and wear resistance under the problem has achieved higher service life and performance.
Patent Information
- Application Number
- CN202411353500.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-07
AI Technical Summary
When used under low speed, large load and certain impact load conditions, the strength and wear resistance are insufficient, resulting in severe wear and short life, making it difficult to meet the application needs of engineering machinery and other applications.
Copper powder, aluminum powder, silicon powder, barium powder, chromium powder, nanomanganese boronide and nanotantalum carbide are prepared in a specific proportion, and high-strength is made through powder mixing, pressing, sintering, heat treatment and vacuum oil immersion. Wear-resistant powder metallurgical bearings.
It improves the strength, wear resistance, corrosion resistance and fatigue resistance of bearings, extends service life, and simplifies the process flow, which is suitable for industrial production.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material powder metallurgy, and in particular to a high-strength and wear-resistant powder metallurgy bearing. Background Art
[0002] Sliding bearings are commonly used parts in various machines and have been widely used in many fields such as automobiles, home appliances, transportation machinery, agricultural machinery, instruments and meters, etc. The ideal sliding bearing material needs to have sufficient compressive strength and fatigue resistance, good friction reduction and wear resistance (small friction coefficient), the function of storing lubricating oil and good running-in properties.
[0003] Existing bearings are usually made of metal powder as raw material using powder metallurgy process. Due to unreasonable selection of metal powder composition and formula, inappropriate selection of powder metallurgy process parameters, etc., they often have low strength performance, insufficient toughness, low hardness, and need to be further improved in heat resistance and corrosion resistance, resulting in wear of bearings and short life. They cannot meet the requirements of bearings working under low speed, large load and certain impact load conditions, such as bearings for oil cylinders of construction machinery such as excavators and bulldozers. It can be seen that how to effectively improve the strength and wear resistance of bearings is particularly important.
[0004] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN103451538B discloses a high-strength and wear-resistant iron-based powder metallurgy bearing material and its preparation method, which is characterized by: in terms of weight percentage, the composition of the material is: copper: 16.0% to 18.0%, carbon: 0.80% to 0.90%, cerium fluoride: 0.01% to 1.0% and the balance of iron, and the total amount of impurities is not more than 2%; the production process of the iron-based powder metallurgy bearing material is powder mixing, pressing, sintering, heat treatment and vacuum oil impregnation. The iron-based powder metallurgy bearing material of the invention has high-strength and wear-resistant characteristics: crushing strength: 720MPa to 780MPa; Rockwell hardness: 90HRB to 110HRB; oil content: 13% to 16%; oil lubrication friction coefficient 0.08 to 0.09; the invention material is used for engineering machinery, such as bearings for oil cylinders of excavators and bulldozers. However, its corrosion resistance and fatigue resistance still need to be further improved.
[0005] Therefore, the development of a high-strength and wear-resistant powder metallurgy bearing with high strength, good wear resistance, good corrosion resistance and fatigue resistance, and long service life meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of powder metallurgy technology of metal materials. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a high-strength wear-resistant powder metallurgy bearing with high strength, good wear resistance, good corrosion resistance and fatigue resistance, and long service life.
[0007] The present invention can be implemented by the following technical solutions:
[0008] A high-strength wear-resistant powder metallurgy bearing according to the present invention is made of the following components in weight percentage: copper powder: 10wt% to 15wt%, aluminum powder: 3wt% to 6wt%, silicon powder: 0.3wt% to 0.8wt%, barium powder: 0.01wt% to 0.03wt%, chromium powder: 0.8wt% to 1.5wt%, nano-manganese boride 0.8wt% to 1.6wt%, nano-tantalum carbide 0.1wt% to 0.3wt%, and the balance is iron powder.
[0009] Preferably, the particle size of the copper powder is 400-800 mesh; the particle size of the aluminum powder is 600-900 mesh; and the particle size of the silicon powder is 500-800 mesh.
[0010] Preferably, the particle size of the barium powder is 400-600 mesh; the particle size of the chromium powder is 800-1200 mesh; and the particle size of the iron powder is 700-1000 mesh.
[0011] Preferably, the particle size of the nano manganese boride is 30-80 nm; the particle size of the nano tantalum carbide is 10-90 nm.
[0012] Another object of the present invention is to provide a method for preparing the high-strength wear-resistant powder metallurgy bearing, comprising the following steps:
[0013] Step S1, weighing each component according to weight percentage, putting them into a mixer and mixing them evenly to obtain a mixed powder;
[0014] Step S2: loading the mixed powder into a mold, pressing to obtain a compact, and then sintering in an inert gas protective atmosphere.
[0015] Step S3: After heat treatment, vacuum oil immersion is performed to obtain a high-strength and wear-resistant powder metallurgy bearing.
[0016] Preferably, the pressing pressure in step S2 is 500-700 MPa.
[0017] Preferably, the inert gas in step S2 is any one of nitrogen, helium, neon and argon.
[0018] Preferably, the sintering temperature in step S2 is 1130° C. to 1280° C., and the sintering time is 1 to 2 hours.
[0019] Preferably, the heat treatment in step S3 includes quenching treatment and tempering treatment performed sequentially.
[0020] Preferably, the quenching temperature of the quenching treatment is 850° C. to 950° C., and the quenching medium is machine oil.
[0021] Preferably, the tempering temperature of the tempering treatment is 200° C. to 250° C., and the tempering time is 1 to 3 hours.
[0022] Preferably, the oil temperature of the vacuum oil immersion is 75°C to 105°C, the vacuum pressure is no more than 6KPa, and the oil immersion time is 50 to 70 minutes.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The method for preparing the high-strength wear-resistant powder metallurgy bearing disclosed in the present invention has a simple process, is easy to operate, does not require special equipment, and does not require the modification of the existing production line. It has low capital investment, high preparation efficiency, and is suitable for continuous industrial production.
[0025] (2) The high-strength wear-resistant powder metallurgy bearing disclosed in the present invention is made of the following components in percentage by weight: copper powder: 10wt% to 15wt%, aluminum powder: 3wt% to 6wt%, silicon powder: 0.3wt% to 0.8wt%, barium powder: 0.01wt% to 0.03wt%, chromium powder: 0.8wt% to 1.5wt%, nano manganese boride 0.8wt% to 1.6wt%, nano tantalum carbide 0.1wt% to 0.3wt%, and the balance is iron powder. Through the reasonable selection of the types and content ratios of the components, the components can cooperate with each other, giving the manufactured bearing products the advantages of high strength, good wear resistance, good corrosion resistance and fatigue resistance, and long service life.
[0026] (3) The high-strength wear-resistant powder metallurgy bearing disclosed in the present invention, the addition of nano manganese boride and nano tantalum carbide can not only improve the strength of the material, but also improve the friction reduction effect. In combination with other components, it can also enhance the anti-seizure performance of the sleeve, thereby extending the service life of the bearing. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0028] Example 1
[0029] A high-strength wear-resistant powder metallurgy bearing is made of the following components in percentage by weight: 10wt% copper powder, 3wt% aluminum powder, 0.3wt% silicon powder, 0.01wt% barium powder, 0.8wt% chromium powder, 0.8wt% nano manganese boride, 0.1wt% nano tantalum carbide, and the remainder is iron powder.
[0030] The particle size of the copper powder is 400 mesh; the particle size of the aluminum powder is 600 mesh; the particle size of the silicon powder is 500 mesh; the particle size of the barium powder is 400 mesh; the particle size of the chromium powder is 800 mesh; the particle size of the iron powder is 700 mesh; the particle size of the nano-manganese boride is 30nm; and the particle size of the nano-tantalum carbide is 10nm.
[0031] A method for preparing the high-strength wear-resistant powder metallurgy bearing comprises the following steps:
[0032] Step S1, weighing each component according to weight percentage, putting them into a mixer and mixing them evenly to obtain a mixed powder;
[0033] Step S2: loading the mixed powder into a mold, pressing to obtain a compact, and then sintering in an inert gas protective atmosphere.
[0034] Step S3: After heat treatment, vacuum oil immersion is performed to obtain a high-strength and wear-resistant powder metallurgy bearing.
[0035] The pressing pressure in step S2 is 500 MPa; the inert gas is nitrogen; the sintering temperature is 1130° C., and the sintering time is 1 h.
[0036] The heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching temperature of the quenching treatment is 850°C and the quenching medium is mechanical oil; the tempering temperature of the tempering treatment is 200°C and the tempering time is 1 hour; the oil temperature of the vacuum oil immersion is 75°C, the vacuum pressure value is not greater than 6KPa, and the oil immersion time is 50 minutes.
[0037] Example 2
[0038] A high-strength wear-resistant powder metallurgy bearing is made of the following components in percentage by weight: copper powder: 12wt%, aluminum powder: 4wt%, silicon powder: 0.5wt%, barium powder: 0.015wt%, chromium powder: 1wt%, nano manganese boride 1wt%, nano tantalum carbide 0.15wt%, and the balance is iron powder.
[0039] The particle size of the copper powder is 500 mesh; the particle size of the aluminum powder is 700 mesh; the particle size of the silicon powder is 600 mesh; the particle size of the barium powder is 450 mesh; the particle size of the chromium powder is 900 mesh; the particle size of the iron powder is 800 mesh; the particle size of the nano-manganese boride is 50nm; and the particle size of the nano-tantalum carbide is 30nm.
[0040] A method for preparing the high-strength wear-resistant powder metallurgy bearing comprises the following steps:
[0041] Step S1, weighing each component according to weight percentage, putting them into a mixer and mixing them evenly to obtain a mixed powder;
[0042] Step S2: loading the mixed powder into a mold, pressing to obtain a compact, and then sintering in an inert gas protective atmosphere.
[0043] Step S3: After heat treatment, vacuum oil immersion is performed to obtain a high-strength and wear-resistant powder metallurgy bearing.
[0044] The pressing pressure in step S2 is 550 MPa; the inert gas in step S2 is helium; the sintering temperature in step S2 is 1160° C., and the sintering time is 1.2 h.
[0045] The heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching temperature of the quenching treatment is 870°C and the quenching medium is mechanical oil; the tempering temperature of the tempering treatment is 220°C and the tempering time is 1.5 hours; the oil temperature of the vacuum oil immersion is 85°C, the vacuum pressure value is not greater than 6KPa, and the oil immersion time is 55 minutes.
[0046] Example 3
[0047] A high-strength wear-resistant powder metallurgy bearing is made of the following components in percentage by weight: copper powder: 13wt%, aluminum powder: 4.5wt%, silicon powder: 0.6wt%, barium powder: 0.02wt%, chromium powder: 1.2wt%, nano manganese boride 1.3wt%, nano tantalum carbide 0.2wt%, and the balance is iron powder.
[0048] The particle size of the copper powder is 600 mesh; the particle size of the aluminum powder is 750 mesh; the particle size of the silicon powder is 650 mesh; the particle size of the barium powder is 500 mesh; the particle size of the chromium powder is 1000 mesh; the particle size of the iron powder is 850 mesh; the particle size of the nano-manganese boride is 60nm; and the particle size of the nano-tantalum carbide is 60nm.
[0049] A method for preparing the high-strength wear-resistant powder metallurgy bearing comprises the following steps:
[0050] Step S1, weighing each component according to weight percentage, putting them into a mixer and mixing them evenly to obtain a mixed powder;
[0051] Step S2: loading the mixed powder into a mold, pressing to obtain a compact, and then sintering in an inert gas protective atmosphere.
[0052] Step S3: After heat treatment, vacuum oil immersion is performed to obtain a high-strength and wear-resistant powder metallurgy bearing.
[0053] The pressing pressure in step S2 is 600 MPa; the inert gas in step S2 is neon; the sintering temperature in step S2 is 1210° C., and the sintering time is 1.5 h.
[0054] The heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching temperature of the quenching treatment is 900°C and the quenching medium is mechanical oil; the tempering temperature of the tempering treatment is 230°C and the tempering time is 2 hours; the oil temperature of the vacuum oil immersion is 90°C, the vacuum pressure value is not greater than 6KPa, and the oil immersion time is 60 minutes.
[0055] Example 4
[0056] A high-strength wear-resistant powder metallurgy bearing is made of the following components in percentage by weight: copper powder: 14wt%, aluminum powder: 5.5wt%, silicon powder: 0.7wt%, barium powder: 0.025wt%, chromium powder: 1.4wt%, nano manganese boride 1.5wt%, nano tantalum carbide 0.25wt%, and the balance is iron powder.
[0057] The particle size of the copper powder is 750 mesh; the particle size of the aluminum powder is 850 mesh; the particle size of the silicon powder is 750 mesh; the particle size of the barium powder is 550 mesh; the particle size of the chromium powder is 1100 mesh; the particle size of the iron powder is 950 mesh; the particle size of the nano-manganese boride is 70nm; and the particle size of the nano-tantalum carbide is 80nm.
[0058] A method for preparing the high-strength wear-resistant powder metallurgy bearing comprises the following steps:
[0059] Step S1, weighing each component according to weight percentage, putting them into a mixer and mixing them evenly to obtain a mixed powder;
[0060] Step S2: loading the mixed powder into a mold, pressing to obtain a compact, and then sintering in an inert gas protective atmosphere.
[0061] Step S3: After heat treatment, vacuum oil immersion is performed to obtain a high-strength and wear-resistant powder metallurgy bearing.
[0062] The pressing pressure in step S2 is 680 MPa; the inert gas in step S2 is argon; the sintering temperature in step S2 is 1260° C., and the sintering time is 1.8 h.
[0063] The heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching temperature of the quenching treatment is 930°C and the quenching medium is mechanical oil; the tempering temperature of the tempering treatment is 240°C and the tempering time is 2.5 hours; the oil temperature of the vacuum oil immersion is 100°C, the vacuum pressure value is not greater than 6KPa, and the oil immersion time is 65 minutes.
[0064] Example 5
[0065] A high-strength wear-resistant powder metallurgy bearing is made of the following components in percentage by weight: copper powder: 15wt%, aluminum powder: 6wt%, silicon powder: 0.8wt%, barium powder: 0.03wt%, chromium powder: 1.5wt%, nano manganese boride 1.6wt%, nano tantalum carbide 0.3wt%, and the balance is iron powder.
[0066] The particle size of the copper powder is 800 mesh; the particle size of the aluminum powder is 900 mesh; the particle size of the silicon powder is 800 mesh; the particle size of the barium powder is 600 mesh; the particle size of the chromium powder is 1200 mesh; the particle size of the iron powder is 1000 mesh; the particle size of the nano-manganese boride is 80nm; and the particle size of the nano-tantalum carbide is 90nm.
[0067] A method for preparing the high-strength wear-resistant powder metallurgy bearing comprises the following steps:
[0068] Step S1, weighing each component according to weight percentage, putting them into a mixer and mixing them evenly to obtain a mixed powder;
[0069] Step S2: loading the mixed powder into a mold, pressing to obtain a compact, and then sintering in an inert gas protective atmosphere.
[0070] Step S3: After heat treatment, vacuum oil immersion is performed to obtain a high-strength and wear-resistant powder metallurgy bearing.
[0071] The pressing pressure in step S2 is 700 MPa; the inert gas in step S2 is nitrogen; the sintering temperature in step S2 is 1280° C., and the sintering time is 2 h.
[0072] The heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching temperature of the quenching treatment is 950°C and the quenching medium is mechanical oil; the tempering temperature of the tempering treatment is 250°C and the tempering time is 3 hours; the oil temperature of the vacuum oil immersion is 105°C, the vacuum pressure value is not greater than 6KPa, and the oil immersion time is 70 minutes.
[0073] Comparative Example 1
[0074] A high-strength wear-resistant powder metallurgy bearing is basically the same as Example 1, except that silicon powder and nano-tantalum carbide are not added.
[0075] Comparative Example 2
[0076] A high-strength wear-resistant powder metallurgy bearing is basically the same as Example 1, except that barium powder and nano-manganese boride are not added.
[0077] At the same time, in order to evaluate the specific technical effects of the high-strength wear-resistant powder metallurgy bearings of the present invention, relevant performance tests were conducted on each example of high-strength wear-resistant powder metallurgy bearings. The test results are shown in Table 1. The test method is as follows:
[0078] (1) Wear resistance: A WTM-2E friction and wear tester was used, GCr15 ball bearing steel was used as the friction pair, the load was 100g, the friction diameter was 8mm, the rotation speed was 200r / min, and the time was 20min; before the experiment, the oxide scale on the surface to be ground was removed to expose the flat surface of the sample, the disc was rotated horizontally, and the sample was in vertical contact with the disc through the upper fixture, and the two rubbed and wore each other. The wear time was 20min to ensure that a stable wear state was achieved; the mass loss was measured using a Sartius Micro electronic balance, and the weight change of the sample during the wear process was studied, and the weight loss rate was calculated to measure the wear resistance of the material. The smaller the weight loss rate, the better the wear resistance.
[0079] (2) Hardness: The reference test standard is GB / T 9097.1-2002 "Determination of apparent hardness of sintered metal materials (excluding cemented carbide) Part 1: Materials with basically uniform cross-sectional hardness". Test 6 points and calculate the average value.
[0080] (3) Crushing strength: The test is carried out in accordance with the standard GB / T6804-2008 “Determination of radial crushing strength of sintered metal bushings”.
[0081] (4) Corrosion resistance: The powder metallurgy bearings were subjected to a salt spray corrosion test at a test temperature of 35°C. A 5% mass concentration sodium chloride aqueous solution was sprayed in the test chamber to simulate the accelerated corrosion environment. The powder metallurgy bearings were qualified for corrosion resistance if their tolerance time (i.e., the time they remained rust-free) exceeded 600 hours. Otherwise, they were unqualified.
[0082] (5) Fatigue resistance: The specimens were subjected to a constant amplitude fatigue test (maximum load 100 MPa, minimum load 20 MPa) on an Amsler HFP-422 high frequency fatigue testing machine, and the fatigue life was recorded and counted.
[0083] Table 1
[0084] project Weight loss rate (%) Hardness(HRB) Crushing strength (MPa) Corrosion resistance Anti-fatigue performance (10,000 times) Example 1 0.22 105 830 qualified 15.6 Example 2 0.18 110 842 qualified 15.8 Example 3 0.16 112 849 qualified 16.2 Example 4 0.13 115 860 qualified 16.3 Example 5 0.11 116 868 qualified 16.5 Comparative Example 1 0.56 92 746 qualified 14.3 Comparative Example 2 0.44 90 760 qualified 14.8
[0085] It can be seen from Table 1 that the high-strength wear-resistant powder metallurgy bearing disclosed in the embodiment of the present invention has better wear resistance, corrosion resistance and fatigue resistance, and higher crushing strength and hardness than the comparative product. The combined addition of silicon powder, nano-tantalum carbide, barium powder and nano-manganese boride is beneficial to improving the above properties.
[0086] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as described above. However, any technician familiar with the profession can make some changes, modifications and evolutions of the technical content disclosed above without departing from the scope of the technical solution of the present invention, which are all equivalent embodiments of the present invention. At the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A high-strength wear-resistant powder metallurgy bearing, characterized in that: The invention is made of the following components in weight percentage: copper powder: 10wt% to 15wt%, aluminum powder: 3wt% to 6wt%, silicon powder: 0.3wt% to 0.8wt%, barium powder: 0.01wt% to 0.03wt%, chromium powder: 0.8wt% to 1.5wt%, nano manganese boride 0.8wt% to 1.6wt%, nano tantalum carbide 0.1wt% to 0.3wt%, and the balance is iron powder.
2. The high-strength wear-resistant powder metallurgy bearing according to claim 1, characterized in that: The particle size of the copper powder is 400-800 mesh; the particle size of the aluminum powder is 600-900 mesh; and the particle size of the silicon powder is 500-800 mesh.
3. The high-strength wear-resistant powder metallurgy bearing according to claim 1, characterized in that: The particle size of the barium powder is 400-600 mesh; the particle size of the chromium powder is 800-1200 mesh; and the particle size of the iron powder is 700-1000 mesh.
4. The high-strength wear-resistant powder metallurgy bearing according to claim 1, characterized in that: The particle size of the nano manganese boride is 30-80nm; the particle size of the nano tantalum carbide is 10-90nm.
5. A method for preparing a high-strength wear-resistant powder metallurgy bearing according to any one of claims 1 to 4, characterized in that: The steps include: Step S1, weighing each component according to weight percentage, putting them into a mixer and mixing them evenly to obtain a mixed powder; Step S2: loading the mixed powder into a mold, pressing to obtain a compact, and then sintering in an inert gas protective atmosphere. Step S3: After heat treatment, vacuum oil immersion is performed to obtain a high-strength and wear-resistant powder metallurgy bearing.
6. The method for preparing a high-strength wear-resistant powder metallurgy bearing according to claim 5, characterized in that: The pressing pressure in step S2 is 500-700 MPa.
7. The method for preparing a high-strength wear-resistant powder metallurgy bearing according to claim 5, characterized in that: The inert gas in step S2 is any one of nitrogen, helium, neon and argon; the sintering temperature in step S2 is 1130° C. to 1280° C., and the sintering time is 1 to 2 hours.
8. The method for preparing a high-strength wear-resistant powder metallurgy bearing according to claim 5, characterized in that: The heat treatment in step S3 includes quenching treatment and tempering treatment performed in sequence.
9. The method for preparing a high-strength wear-resistant powder metallurgy bearing according to claim 8, characterized in that: The quenching temperature of the quenching treatment is 850°C to 950°C, and the quenching medium is mechanical oil; the tempering temperature of the tempering treatment is 200°C to 250°C, and the tempering time is 1 to 3 hours.
10. The method for preparing a high-strength wear-resistant powder metallurgy bearing according to claim 5, characterized in that: The oil temperature of the vacuum oil immersion is 75° C. to 105° C., the vacuum pressure value is not greater than 6 KPa, and the oil immersion time is 50 to 70 minutes.
Citation Information
Patent Citations
High-strength wearproof iron-based powder metallurgy bearing material and preparation method thereof
CN103451538B